Islamic development model: a shift from growth-driven to prosperity-driven model / Hassan Mad - Mad, Hassan (Faculty of Buness and Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
Islamic development model is nothing new. The formulation of the Medina Charter for example, is a classical case of a noble initiative taken by Prophet Muhammad (pbuh). The Charter, the first written legal framework of any enactment or by-law in the world, is to govern the Islamic development model but taking into consideration the presence of the non-Muslim in the Muslim-led plural community. While the Muslim is governed by the Maqasid Syariah and other syariah rules, the Medina Charter is to accommodate the others, within the Islamic legal framework, be it in business or in any other endeavours. Since then, not that many global initiatives led by the Muslim that we can be proud of.